ANALISA FAKTOR KESELAMATAN DAN KESEHATAN KERJA (K3) YANG MEMPENGARUHI KECELAKAAN KERJA PADA PEKERJAAN PEMBANGUNAN SMPN 038 SAMARINDA - SAPUTRA, RYAN (KURVA S JURNAL MAHASISWA, 2018)
In carrying out project work, PT. Qirelis Mandiri Jaya as a company engaged in construction has never been separated from the risk of workplace accidents, so that in the implementation of the development project, a good management of Occupational Health and Safety (K3) is needed, because the implementation of K3 can prevent and reduce accident factors work in a project. Based on the problems found, namely what are the factors of occupational safety and health that affect the occurrence of work accidents in the construction project of Samarinda 038 Junior High School? Analysis of the data used is the analysis of severity index methods and probability impact matrix analysis of answers to questionnaires distributed to 30 respondents from the Project Manager, Field Executors, Field Supervisors and Workers who know the conditions and are directly involved in the project development work. Based on the results of research using probability impact matrix method found that there are 2 factors that significantly affect the occurrence of work accidents in the project, these variables are obtained from the highest level of risk variables, namely not wearing Personal Protective Equipment (X2.3) and Signs or posters of K3 warnings not there are / are not installed according to the applicable provisions (X4.2).